2023
DOI: 10.1097/md.0000000000032938
|View full text |Cite
|
Sign up to set email alerts
|

Hypoalbuminemia and colorectal cancer patients: Any correlation?: A systematic review and meta-analysis

Abstract: Background: In malnourished patients with colorectal cancer, hypoalbuminemia is common and was proposed to determine the postoperative outcome of colorectal surgery. Mounting articles published but have not been evaluated. We aim to assess the predictive value of preoperative hypoalbuminemia in patients undergoing colorectal surgery.Methods: We performed a literature search from PubMed, Euro PMC, and Cochrane with the terms serum albumin, hypoalbuminemia, prognosis, outcome, colorectal cancer, and neoplasm. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 38 publications
2
6
0
1
Order By: Relevance
“…Based on our study’s findings, we can conclude that preoperative serum albumin level is a useful prognostic biomarker for CRC patient outcomes after surgery. These findings are aligned with previous studies in the literature that have shown the association between hypoalbuminemia and poor surgical outcomes [ 10 - 12 ]. One example of such studies is a paper that analyzed patients who have undergone significant gastrointestinal surgery [ 13 ].…”
Section: Discussionsupporting
confidence: 92%
“…Based on our study’s findings, we can conclude that preoperative serum albumin level is a useful prognostic biomarker for CRC patient outcomes after surgery. These findings are aligned with previous studies in the literature that have shown the association between hypoalbuminemia and poor surgical outcomes [ 10 - 12 ]. One example of such studies is a paper that analyzed patients who have undergone significant gastrointestinal surgery [ 13 ].…”
Section: Discussionsupporting
confidence: 92%
“…25 The impact of preoperative hypoalbuminemia on surgical outcomes has long been established for colorectal and non-colorectal surgery. [26][27][28] Supporting our findings, a recent retrospective analysis of 208 patients who underwent surgery for UC also found that preoperative transfusion and preoperative hypoalbuminemia (≤2.4 g/ dl, in said study) were predictors of severe complications and SSI. 29 We showed that hypoalbuminemia impacts postoperative morbidity in all patients, regardless of age.…”
Section: Discussionsupporting
confidence: 84%
“…Malnutrition can directly influence host immunity and, therefore, cancer outcomes [39]. Individually, hypoalbuminemia alone has been associated with poor prognosis in cancer patients [11]; however, since other confounders and diseases can easily alter albumin levels, it has now been used in combination with other variables. Combination with lymphocytes generates an immune-nutrition marker (PNI) as lymphocyte counts are reflective of cell-mediated immunity and are a vital component of cancer defense.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows poor survival, increased complications, and higher healthcare costs among cancer patients suffering from malnutrition [6]. Given that up to 71% of cancer patients may be malnourished before treatment [7], a plethora of research is being conducted to accurately identify malnourished cancer patients so that early interventions can be administered to improve prognosis [8][9][10][11][12]. Nevertheless, there is no clarity on which is the best biomarker for identifying malnutrition and predicting outcomes in cancer patients [13].…”
Section: Introductionmentioning
confidence: 99%